2019
DOI: 10.1111/jfpp.13875
|View full text |Cite
|
Sign up to set email alerts
|

Molecular monitoring of disinfection efficacy of E. coli O157:H7 in bottled purified drinking water by quantitative PCR with a novel dye

Abstract: A new method was developed using a novel dye thiazole orange monoazide (TOMA) combined with quantitative real‐time PCR (qPCR) to detect viable Escherichia coli O157:H7 cells. Different from the commonly used PMA‐qPCR assay that is based on membrane integrity, this TOMA‐qPCR method is based on the concept of metabolic activity. TOMA consists of three components: a nucleic acid‐intercalating moiety, a crosslinkable moiety and a linker. TOMA concentration at 50 μg/ml, 20 min incubation time, and 30 min light expo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
2

Year Published

2019
2019
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 26 publications
1
7
0
2
Order By: Relevance
“…However, the PCR signal of L. monocytogenes DNA activated with PMAxx (75 µM) obtained from chorinetreated cells was not completely inactivated, showing a Ct value below the LOD (Figure 3). Our results agree with a previous study that observed that PMA-qPCR assay (PMA at 50 µM for 20 min of incubation at 37 • C) did not reduce the signal of chlorine-killed cells of E. coli O:157 H7 (10 4 cfu/ml) artificially inoculated in drinking water (Cao et al, 2019a). Based on these results, new experiments were performed under different conditions of time/temperature for the incubation of the DNA with the dye.…”
Section: V-qpcr Combined With Pmaxx + Emasupporting
confidence: 91%
“…However, the PCR signal of L. monocytogenes DNA activated with PMAxx (75 µM) obtained from chorinetreated cells was not completely inactivated, showing a Ct value below the LOD (Figure 3). Our results agree with a previous study that observed that PMA-qPCR assay (PMA at 50 µM for 20 min of incubation at 37 • C) did not reduce the signal of chlorine-killed cells of E. coli O:157 H7 (10 4 cfu/ml) artificially inoculated in drinking water (Cao et al, 2019a). Based on these results, new experiments were performed under different conditions of time/temperature for the incubation of the DNA with the dye.…”
Section: V-qpcr Combined With Pmaxx + Emasupporting
confidence: 91%
“…In viable cells, with an intact envelope, the v-qPCR dye cannot penetrate inside and thus its DNA is free for amplification in a subsequent qPCR assay. A number of v-qPCR dyes have been developed for viability studies: EMA (ethidium monoazide), PMA (propidium monoazide) [ 45 ], and TOMA (thiazole orange monoazide) [ 46 ]. The utility of the PMA v-qPCR method has been demonstrated for evaluating the efficiency of water disinfection, sensitivity of M. avium ssp.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, the "viability-PCR" approach has been proposed as an alternative method to RT-qPCR, based on the treatment of the sample with DNA intercalating dye, ethidium monoazide (EMA) or propidium monoazide (PMA) or thiazole orange monoazide (TOMA) which penetrates only into cells with damaged membranes or binds to free DNA, inhibiting subsequent amplification. These results related to the amplification show that living cells with intact membranes are viable (Cao et al, 2018;Gobert et al, 2018;Scariot et al, 2018).…”
Section: Resultsmentioning
confidence: 71%